2012
DOI: 10.1093/qje/qjs034
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Deforestation in the Tropics*

Abstract: Tropical deforestation accounts for almost one-…fth of greenhouse gas emissions and threatens the world's most diverse ecosystems. Much of this deforestation is driven by illegal logging. We use novel satellite data that tracks annual deforestation across eight years of Indonesian institutional change to examine how local o¢ cials'incentives a¤ect deforestation. Increases in the number of political jurisdictions lead to increased deforestation and lower timber prices, consistent with Cournot competition betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(98 citation statements)
references
References 32 publications
(32 reference statements)
1
75
1
2
Order By: Relevance
“…The same phenomenon is also associated with changes in governmental and corporate leadership when concession maps are commonly redrawn and previous harvest plans are disregarded. Furthermore, in anticipation of unfavorable treatment by newly installed governments, logging companies often harvest as much timber as possible prior to or during elections (Burgess et al, 2012). Future climate agreements should include binding agreements that validated projects adopting RIL shall not be interrupted before the end of a harvest cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The same phenomenon is also associated with changes in governmental and corporate leadership when concession maps are commonly redrawn and previous harvest plans are disregarded. Furthermore, in anticipation of unfavorable treatment by newly installed governments, logging companies often harvest as much timber as possible prior to or during elections (Burgess et al, 2012). Future climate agreements should include binding agreements that validated projects adopting RIL shall not be interrupted before the end of a harvest cycle.…”
Section: Discussionmentioning
confidence: 99%
“…If such devolution means an end to access to resources outside the district, then local authorities may find it necessary to open up natural resources, such as forests, to exploitation in order to satisfy material needs. Burgess et al (2012) found this to be the case as new districts were formed as part of the decentralization process in Indonesia. A recent example comes with the creation of the new province, North Kalimantan, in Borneo, Indonesia.…”
Section: Unintended Consequences and Moderating Factors For Dfmmentioning
confidence: 99%
“…For instance, consistent with this paper's findings, Rasul and Rogger (2013) report significant gains from providing Nigerian bureaucrats autonomy in decision-making. Other papers note, to the contrary, bureaucrats and politicians may misuse discretion in environmental regulation (Burgess, Hansen, Olken, Potapov, and Sieber (2012), Jia (2014)). 7 The GPCB follows a government classification for plants based on their reported scale of capital investment, with small scale being investment less than INR 50m ($1 million), medium, INR 50-100m ($1-2 million), plants were inspected at less than the prescribed rate.…”
Section: Context: Regulation Of Industrial Pollution In Indiamentioning
confidence: 99%